2016
DOI: 10.1038/mt.2016.7
|View full text |Cite
|
Sign up to set email alerts
|

Specific Reactivation of Latent HIV-1 by dCas9-SunTag-VP64-mediated Guide RNA Targeting the HIV-1 Promoter

Abstract: HIV-1 escapes antiretroviral agents by integrating into the host DNA and forming a latent transcriptionally silent HIV-1 provirus. Transcriptional activation is prerequisite for reactivation and the eradication of latent HIV-1 proviruses. dCas9-SunTag-VP64 transcriptional system has been reported that it can robustly activate the expression of an endogenous gene using a single guide RNA (sgRNA). Here, we systematically investigated the potential of dCas9-SunTag-VP64 with the designed sgRNAs for reactivating la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 50 publications
2
67
0
Order By: Relevance
“…YA cells and C11 cells, which are HIV-1-infected or latently infected Jurkat T cells, respectively, were first created in our laboratory and are now used widely in the research community 36, 37, 51, 52, 53, 54. The C11 and YA cells were maintained in RPMI 1640 medium supplemented with 10% (v/v) fetal bovine serum (Gibco), 100 U mL −1 penicillin, and 100 μg mL −1 streptomycin (Invitrogen) at 37°C under 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…YA cells and C11 cells, which are HIV-1-infected or latently infected Jurkat T cells, respectively, were first created in our laboratory and are now used widely in the research community 36, 37, 51, 52, 53, 54. The C11 and YA cells were maintained in RPMI 1640 medium supplemented with 10% (v/v) fetal bovine serum (Gibco), 100 U mL −1 penicillin, and 100 μg mL −1 streptomycin (Invitrogen) at 37°C under 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…dCas9 transcriptional effectors have even been used to efficiently mediate repression and activation of endogenous genes in Drosophila (Lin et al 2015b) and in plant cells (Piatek et al 2015). Both TALE and Cas9 activators have also been configured to stimulate transcription of latent HIV Ji et al 2016;Limsirichai et al 2016;Perdigao et al 2016;Saayman et al 2016), indicating their potential to work in concert with antiretroviral therapy for eradicating HIV infection. Importantly, because of the ease with which the CRISPRCas9 system can be used, genome-wide screens using Cas9 transcriptional activators (Gilbert et al 2014;Konermann et al 2015) and repressors (Gilbert et al 2014) can be easily implemented to discover genes involved in a number of diverse processes, including drug resistance and cancer metastasis.…”
Section: Applications Of Targeted Transcriptional Regulationmentioning
confidence: 99%
“…They showed that targeting of different regions of LTR particularly LTR promoter could lead to activation of viral gene expression in cell line models of HIV-1 latency. [123][124][125][126] 2 | DISCUSSION Genome editing using CRISPR/Cas9 represents a powerful strategy to treat various diseases including viral infections. In this study, we provide key insights into the mechanism and application of CRISPR/ Cas9 in eradication and limitation of several DNA viruses from different cell lines.…”
Section: Vacvmentioning
confidence: 99%
“…Several studies employed CRISPR/dCas9 system (a deactivated Cas9 nuclease bonded to transcription activators) to induce activation of dormant HIV provirus. They showed that targeting of different regions of LTR particularly LTR promoter could lead to activation of viral gene expression in cell line models of HIV‐1 latency …”
Section: Introductionmentioning
confidence: 99%